Determinants of Net Exports in Polish and Czech Manufacturing: A Sectoral Approach with Error Correction Model - Magdalena Olczyk; Aleksandra Kordalska (Institute of Economic Research (IER), 2017)
Growth model in CEE countries has based on a massive inflow of direct foreign investments, especially in manufacturing, from the onset of the transformation. This resulted in a substantial share of manufacturing goods in total exports and a high ranking position of some CEE countries among the most industrialized economies in the world. The main objective of this paper is to compare the determinants of the international competitiveness, measured by the net exports of the manufacturing sectors in the Czech and Polish economies, by using the database of 13 manufacturing sub-sectors in 1995-2011. The authors research the question of how much foreign and domestic demand, the level of labour costs, the level of sector innovation intensity, the level of sector openness to foreign markets as well as sectoral labour productivity influence the changes in trade balance. Our approach is based on employing an error correction model and SURE model to disaggregated sectoral manufacturing data. The results of the analysis conducted show substantial differences in the roles particular variables play in explaining the net exports in individual sectors. For the majority of Polish and Czech manufacturing sub-sectors, generation of positive trade balance is determined by relative demand growth. An increasing labour productivity influences heavily a positive trade balance of Polish goods in majority of sub-sectors, however, a key factor in Czech sub-sectors is decreasing unit labour costs. The results of the analysis indicate mostly a greater impact of the researched factors on net exports in long rather than short term and the better capacity of the Czech economy to correct deviations from the equilibrium.
Keywords: F40; C23; F14; O14; L60; 330; CEE economies; net exports; international competitiveness; manufacturing; error correction mode